2016
DOI: 10.1177/1012690216637630
|View full text |Cite
|
Sign up to set email alerts
|

In-ger-land, In-ger-land, In-ger-land! Exploring the impact of soccer on the sense of belonging of those seeking asylum in the UK

Abstract: This document is the author deposited version. You are advised to consult the publisher's version if you wish to cite from it. Published versionWOODHOUSE, Donna and CONRICODE, Dominic (2017). 'In-ger-land, In-ger-land, In-ger-land! : exploring the impact of soccer on the sense of belonging of those seeking asylum in the UK. International Review for the Sociology of Sport, 52 (8), 940-954. Copyright and re-use policySee http://shura.shu.ac.uk/information.html Sheffield Hallam University Research Archivehttp://s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…Previous studies have addressed asylum seekers' participation in non-formal settings such as popular education (Morrice et al 2017, Smith 2013, L opez-Bech and Z uniga 2017, but from the results of this study, we stress that adult asylum seekers are limited to participating in non-formal CoPs. Such engagement, however, can be both an opportunity and a trap; the opportunity is to expand social networks and learn (Woodhouse andConricode 2017, Sorgen 2015), while the trap is to engage only with other asylum seekers and thus become isolated from the local community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have addressed asylum seekers' participation in non-formal settings such as popular education (Morrice et al 2017, Smith 2013, L opez-Bech and Z uniga 2017, but from the results of this study, we stress that adult asylum seekers are limited to participating in non-formal CoPs. Such engagement, however, can be both an opportunity and a trap; the opportunity is to expand social networks and learn (Woodhouse andConricode 2017, Sorgen 2015), while the trap is to engage only with other asylum seekers and thus become isolated from the local community.…”
Section: Discussionmentioning
confidence: 99%
“…L opez-Bech and Z uniga (2017) stress that storytelling is a way to give voice to asylum seekers that also builds bridges between them and locals and thereby facilitates integration. Woodhouse and Conricode (2017) claim that playing football is important for male asylum seekers' sense of belonging, control, and identity-formation. Sorgen (2015) finds that participation in an informal English conversation club based on mutual accommodation has been a key factor in cultivating social networks and support.…”
Section: Previous Research About Asylum Seekers Learning To Belongmentioning
confidence: 99%
“…Only three studies demonstrated an explicit awareness of the need to make the assumptions and categorizations of policy makers visible and open to inspection. While Woodhouse and Conricode ( 2017 : p. 941) acknowledge that the term “asylum seeker” is used in legal and popular discourse, they instead used the phrase “people seeking asylum” in response to “participants' attempts to articulate identities on their own terms and their highlighting of the limiting nature and negative perceptions of the term ‘asylum seeker'.” Dukic et al ( 2017 ) use the term “people seeking asylum” for the same reason. In a similar vein, Amara et al ( 2004 ) categorize refugees as newly established minorities.…”
Section: Fundamental Concepts Issues and Problemsmentioning
confidence: 99%
“…In sports court space (Figure 11), physical activity mediated engagement with the park, while physical activity was mainly influenced by sports court, accessibility, tree cover, and space enclosure. Previous evidence had shown that physical activity such as basketball, badminton, and square dancing had a positive impact on deep interaction [20,21,64], which was intrinsic to the influence of sports court on individuals' park engagement. The spaces near park entrances were more preferred by users, and directly linked the relation between accessibility and physical activity.…”
Section: Sports Court Space: Engagement With the Park Is Mediated By Physical Activity And Directly Influenced By Crowds Congregatementioning
confidence: 99%
“…As more and more residents tend to visit community sports parks for physical activities [17], opportunities for neighborhood contact and social interaction increase significantly, which can be achieved by the following two ways: First, physical activity mostly requires teamwork that offers good training opportunities for cultivating interpersonal communication skills [18,19]. It is a deeper and more intimate form of social interaction and can bring various socioeconomic and ethnic groups together, especially basketball and square dancing [20][21][22]. Second, physical activity have the function of upgrade self-efficacy and reduces social anxiety [18].…”
Section: Introductionmentioning
confidence: 99%